The Effect of Concept Visualisation on Critical Thinking Skills in Science Learning Among Malaysian Primary School Children - Lily Premala, Michael (2023)
It was necessary to promote critical thinking skills among students because a lack of critical thinking skills among students had been a persistent drawback in primary science education. According to studies, the idea visual image was used to improve critical thinking skills with some techniques being more practical than others. The study’s goal was to determine whether conception mapping (a conception visual image technique) was an effective technique for developing essential thinking ability in science learning among Malaysian primary school children. For this purpose, students using concept mapping were compared to students using mind mapping (the existing visualisation technique). A quasi-experimental methodology was used with a total of seventy students; thirty-five students in the mind map class and the remaining was in the concept map class. The concept map class used concept mapping strategy while the mind map class used mind mapping strategy. The two classes were given a pre-test and a post-test on their science achievement and critical thinking skills. The gain score means for science achievement and critical thinking skill in both groups were compared using independent t-test and descriptive statistics. In learning science, a satisfaction questionnaire and a behavioural checklist were also used to assess students’ attitudes and interactions with concept mapping and mind mapping. The data analysis results showed that the gain score means for the concept map class were greater than the gain score means of the mind map class on science achievement as well as critical thinking with p< .05 indicating statistical significance. In addition, students in the concept map class were more positive about the visualisation technique used than students in the mind map class (p< .05). As a result, the findings supported the conclusion that the concept mapping strategy was more effective in improving students’ critical thinking skills and science learning. Thus, concept mapping was preferred over mind-mapping as a classroom learning tool for science teaching and learning in primary schools to support science learning and the development of critical thinking skills.